Close-range photogrammetry and 3D imaging - Luhmann, T.; Robson, Stuart (Engineering professor); Kyle, Stephen (Engineering professor); Boehm, Jan (Engineering professor) (De Gruyter, 2020)
This is the third edition of the well-known guide to close-range photogrammetry. It provides a thorough presentation of the methods, mathematics, systems and applications which comprise the subject of close-range photogrammetry, which uses accurate imaging techniques to analyse the three-dimensional shape of a wide range of manufactured and natural objects.- Resumé vydavatel
"The first edition of 'Close Range Photogrammetry' was published in 2006 by Whittles Publishing. This was a translated and extended version of the original German book 'Nahbereichsphotogrammetrie...'"--Preface.
Keywords: fotogrammetrie; digitální fotogrammetrie; photogrammetry; digital photogrammetry; elektronické knihy; učebnice; electronic books; textbooks